2015
DOI: 10.1371/journal.pone.0128365
|View full text |Cite
|
Sign up to set email alerts
|

Brown Pine Leaf Extract and Its Active Component Trans-Communic Acid Inhibit UVB-Induced MMP-1 Expression by Targeting PI3K

Abstract: Japanese red pine (Pinus densiflora) is widely present in China, Japan, and Korea. Its green pine leaves have traditionally been used as a food as well as a coloring agent. After being shed, pine leaves change their color from green to brown within two years, and although the brown pine leaves are abundantly available, their value has not been closely assessed. In this study, we investigated the potential anti-photoaging properties of brown pine leaves for skin. Brown pine leaf extract (BPLE) inhibited UVB-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Huh et al [12] also reported that brown pine leaf extracts, including DAA and trans -communic acid, inhibit UVB-induced MMP-1 expression in a human keratinocyte cell line (HaCaT). Unlike previous studies based on biochemical assays of other antiaging biomarkers, our study focused more on the cellular efficacy of DAA on morphological changes of intact collagen fibers in a 3D human skin environment.…”
Section: Resultsmentioning
confidence: 99%
“…Huh et al [12] also reported that brown pine leaf extracts, including DAA and trans -communic acid, inhibit UVB-induced MMP-1 expression in a human keratinocyte cell line (HaCaT). Unlike previous studies based on biochemical assays of other antiaging biomarkers, our study focused more on the cellular efficacy of DAA on morphological changes of intact collagen fibers in a 3D human skin environment.…”
Section: Resultsmentioning
confidence: 99%
“…It is generated from primary human keratinocytes on a collagen substrate containing HDFs [16,17]. It is grown at the air-liquid interface where epidermal-dermal interactions occur, and it allows full epidermal stratification.…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al [ 8 ] reported that resveratrol decreases the activity of phosphatidylinositide 3-kinase (PI3K), an upstream kinase of Akt, in vitro . Furthermore, it has been reported that inhibition of PI3K activity decreases Akt signaling [ 6 ], and numerous other studies have reported similar findings in various cell lines [ 13 26 ]. Based on these previous reports, we propose that resveratrol might target PI3K activity to attenuate Akt signaling pathway in Huh7-HBx cells.…”
Section: Discussionmentioning
confidence: 57%